2010
DOI: 10.5194/acpd-10-30129-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vertical profiles of nitrous acid in the nocturnal urban atmosphere of Houston, TX

Abstract: Nitrous acid (HONO) often plays an important role in tropospheric photochemistry as a major precursor of the hydroxyl radical (OH) in early morning hours and potentially during the day. However, the processes leading to formation of HONO and its vertical distribution at night, which can have a considerable impact on daytime ozone formation, are currently poorly characterized by observations and models. Long-path differential optical absorption spectroscopy (LP-DOAS) measurements of HONO during the 2006 TexAQS … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 48 publications
5
50
1
Order By: Relevance
“…Using a 1D chemistry and transport model, Wong et al (2011) showed that this mechanism, together with an accurate description of vertical mixing, is able to successfully explain the nocturnal HONO observations in Houston. This mechanism also seems to depend on the amount of water adsorbed on the surface, i.e.…”
Section: Heterogeneous Pathways For Atmospheric Hono Formationmentioning
confidence: 94%
See 2 more Smart Citations
“…Using a 1D chemistry and transport model, Wong et al (2011) showed that this mechanism, together with an accurate description of vertical mixing, is able to successfully explain the nocturnal HONO observations in Houston. This mechanism also seems to depend on the amount of water adsorbed on the surface, i.e.…”
Section: Heterogeneous Pathways For Atmospheric Hono Formationmentioning
confidence: 94%
“…the relative humidity, as pointed out by Stutz et al (2004). Vertical nighttime profile measurements (e.g., Kleffmann et al, 2003;Wong et al, 2011;VandenBoer et al, 2013) suggest that NO 2 to HONO conversion on the ground is the dominant source of nocturnal HONO.…”
Section: Heterogeneous Pathways For Atmospheric Hono Formationmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this mechanism is still under discussion and does not significantly seem to contribute to the atmospheric HONO formation (Crowley and Carl, 1997;Carr et al, 2009;Amedro et al, 2011;Sörgel et al, 2011;Wong et al, 2011). Recently, Bejan et al (2006) and Kleffmann (2007) proposed the gas-phase HONO production during the photolysis of aromatic compounds containing ortho-nitrophenols and a noontime HONO production of 100 ppt h −1 was estimated for urban conditions.…”
Section: Introductionmentioning
confidence: 95%
“…contributes to significant HONO amounts under conditions of elevated NO concentrations, particularly during daytime Volkamer et al, 2010;Wong et al, 2011), but this process competes with photolysis. Most recently Li et al (2008) showed that HONO can be formed upon the gas-phase reaction of photolytically excited NO 2 with water:…”
Section: Introductionmentioning
confidence: 95%